2017
DOI: 10.1021/acsbiomaterials.7b00281
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Structure-Based Prediction of How ATRP Initiators React with Proteins

Abstract: The growth of polymers from the surface of proteins via controlled radical polymerization depends on the attachment of small molecule initiators to amino acid residues. Our ability to control and harness the power of polymer-based protein engineering is reliant on the accuracy of prediction where and how fast atom transfer radical polymerization (ATRP) initiators will react with a protein surface. We performed a systematic characterization of the reaction between a bromine-functionalized N-hydroxysuccinimide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 65 publications
(111 reference statements)
1
81
1
Order By: Relevance
“…Differences in polymer–protein hybrid behavior were manifested in enzyme activity assays, indicating that responsive polymer–protein block copolymers of varied structures, architectures, and solution behavior can be used to control bioconjugate activity . The conjugates exhibited dramatic increases in enzyme stability over a wide range of temperatures indicating that one can manipulate enzyme kinetics and stability using polymer‐based protein engineering …”
Section: Control Of Macromolecular Architecturementioning
confidence: 99%
“…Differences in polymer–protein hybrid behavior were manifested in enzyme activity assays, indicating that responsive polymer–protein block copolymers of varied structures, architectures, and solution behavior can be used to control bioconjugate activity . The conjugates exhibited dramatic increases in enzyme stability over a wide range of temperatures indicating that one can manipulate enzyme kinetics and stability using polymer‐based protein engineering …”
Section: Control Of Macromolecular Architecturementioning
confidence: 99%
“…Russell, Matyjaszewski, and co-workers studied conjugation of ATRP initiators to lysozyme and chymotrypsin, and concluded that a lysine must be sufficiently exposed; in addition, the microenvironment such as the presence of adjacent lysine and local charge affects the reactivity. 36 Bernardes, Jiménez-Osés, and co-workers used a sulfonyl acrylate reagent to selectively modify a single lysine in five different proteins (human serum albumin, synaptotagmin-I C2A domain, lysozyme, annexin-V, and trastuzumab). 37 High reactivity of the reagent allowed the most acidic lysine to be selectively modified at pH 8, and the conjugation reached complete conversion using equimolar amounts of the reagent.…”
Section: Choosing the Right Conjugation Chemistrymentioning
confidence: 99%
“…S3 † ). The number of polymers is estimated based on predicted reactivities 37 and conjugation sites observed by MALDI-TOF (Table S2 † ). CD gives the mean density of secondary structural elements (α-helices, β-strands, and coils) in a given system.…”
Section: Resultsmentioning
confidence: 99%